Economic implications of emotional marketing based on consumer loyalty of mobile phone brands: the sequential mediating roles of brand identity and brand trust - Jiang, Yaping; Sun, Yanyan; Tu, Shibo (Technological and Economic Development of Economy, 2023)
With the advent of digital technology and social media, mobile phone companies are increasingly turning to emotional marketing to appeal to consumers’ inner preferences. The purpose of this study is to examine the economic consequences of emotional marketing on customer loyalty, while taking into account the mediating variables of brand identity and brand trust. By surveying 647 digitally-savvy consumers in China, the proposed model was empirically validated. The results suggest that emotional marketing plays a crucial role in fostering consumer loyalty towards mobile phone brands, and that brand identity and brand trust play sequential mediating roles in the impact of emotional marketing on consumer loyalty. This research enhances our understanding of emotional marketing and consumer loyalty, and offers valuable insights for mobile phone brands seeking to implement effective emotional marketing strategies.